Profil Proliferasi Sel Limfosit Benalu Batu (Begonia medicinalis) Asal Kabupaten Morowali UTARA Provinsi Sulawesi Tengah - Akhmad Khumaidi; Agustinus Widodo; Arsa Wahyu Nugrahani; Ediati Sasmito; Nanang Fakhrudin (Fakultas Farmasi Universitas Pancasila, 2020)
The plant of Benalu Batu (Begonia medicinalis) from the North Morowali regency has been used empirically and is known to have anticancer activity. The study aims to determine the profile of the activity of lymphocytes cell proliferation of extracts and fractions of Benalu Batu in vitro as well to measure the correlation of total flavonoid content against the stimulating index of lymphocytes cell proliferation. The extraction of simplicia by using the maceration method with methanol solvent. The liquid-liquid partition method is used in the fractionation of methanol extracts with hexane, ethyl acetate, and water solvents, sequentially. Test of lymphocytes cell proliferation using MTT reduction (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) method with concentration series 10, 20, 50, and 100 μg/mL. The total of flavonoids content of extracts and fractions were determined by using colorimetric method. The stimulation index (IS) is used in measuring the activity of lymphocytes cell proliferation. The test results showed that the methanol extracts, hexane fraction, ethyl acetate, and water may increase the proliferation of lymphocytes in the entire test concentration. The concentration of test influences on increasing the stimulation of the proliferation of lymphocytes cells. A test concentration of 100 μg/mL has the highest stimulation index on each test sample and its stimulant index value of hexane fraction, ethyl acetate fraction, methanol fraction and water fraction were 10.12, 6.56, 4.82, and 4.17, respectively. Total flavonoids content and stimulation indices have very low correlation (r = 0,082) and concentrations of 10 μg/mL have the highest correlation coefficient (r2 = 0.18). The results showed that the hexane and ethyl acetate fractions can be developed as immunostimulant materials for the anticancer supportive therapeutic agents despite having a very low correlation to the flavonoid levels.